Analisis Peran Akuntan Manajemen, Auditor, dan Whistleblower dalam Mengungkap Korupsi Melalui Metode Whistleblowing - Ayu Dyah Nirmalasari; Ajeng Tita Nawangsari (AKUNTANSI 45, 2026)
This research aims to analyze the role of management accountants, auditors, and Whistleblowers in exposing corrupt practices through Whistleblowing mechanisms. The high level of corruption in Indonesia demands a more effective strategy, where the three roles have a strategic position in detecting and reporting irregularities. This study uses a qualitative approach with the literature review method, focusing on the analysis of concepts, roles, and relationships between actors based on theories, regulations, and findings of previous research. Management accountants contribute by providing internal information and financial evidence that indicates fraud. Auditors, both internal and external, ensure accountability through independent audits of such reports and evidence. Meanwhile, Whistleblowers have a crucial role in uncovering corruption cases, although they often face significant risks in the form of threats or attacks from those who feel threatened. The results of the study confirm that synergy between management accountants, auditors, and Whistleblowers can strengthen the effectiveness of the Whistleblowing system in preventing and exposing corruption. Thus, this research contributes to the development of a more comprehensive anti-corruption strategy, as well as emphasizing the importance of Whistleblower protection as an integral part of a transparent and accountable oversight system.